2010
DOI: 10.1523/jneurosci.4565-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Inositol Triphosphate Is Molecular Correlate of Working Memory in Nonhuman Primates

Abstract: Working memory (WM) is a process of actively maintaining information in the mind for a relatively short period of time, and prefrontal cortex (PFC) has been thought to play a central role in its function. However, our understanding of underlying molecular events that translate into WM behavior remains elusive. To shed light on this issue, we have used three distinct nonhuman primate models of WM where each model represents three WM conditions: normal control, WM-deficient, and recuperated to normal from WM def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Among the 18 pairs are those involving PLCH1 , a member of the eta family of the phosphoinositide-specific phospholipase C (PLC), and PDE1A , a Ca 2+ /Calmodulin-dependent phosphodiesterase (PDE). Both PLCs and PDEs are strongly implicated in the molecular mechanisms of working memory, such as the G-protein-coupled responses to neurotransmitters, which lead to Ca 2+ release as the inositol trisphosphate concentration increases [26, 27], or cAMP/cGMP signaling in dopaminergic, cholinergic and serotonergic neurotransmission [28, 29]. Further significant interaction candidates include the zinc-dependent aminopeptidase LNPEP together with the xylosyltransferase GXYLT1 , neurexin NRXN1 , a cell adhesion molecule and receptor associated with schizophrenia [30] or RBFOX1 , which regulates human neuronal development [31].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 18 pairs are those involving PLCH1 , a member of the eta family of the phosphoinositide-specific phospholipase C (PLC), and PDE1A , a Ca 2+ /Calmodulin-dependent phosphodiesterase (PDE). Both PLCs and PDEs are strongly implicated in the molecular mechanisms of working memory, such as the G-protein-coupled responses to neurotransmitters, which lead to Ca 2+ release as the inositol trisphosphate concentration increases [26, 27], or cAMP/cGMP signaling in dopaminergic, cholinergic and serotonergic neurotransmission [28, 29]. Further significant interaction candidates include the zinc-dependent aminopeptidase LNPEP together with the xylosyltransferase GXYLT1 , neurexin NRXN1 , a cell adhesion molecule and receptor associated with schizophrenia [30] or RBFOX1 , which regulates human neuronal development [31].…”
Section: Resultsmentioning
confidence: 99%
“…Birnbaum et al noted that PKC overactivation via G aq -coupled receptors within the PFC impaired working memory function (2004). Other downstream effectors of the G aq signaling cascade have also been implicated in working memory function, such as IP 3 within the PFC (Lopez-Tellez et al, 2010). D1 receptors within the PFC also play a significant role in working memory (Sawaguchi and Goldman-Rakic, 1991;Williams and Goldman-Rakic, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We, as well as others, have observed that chronic haloperidol administration induces WM deficit in both young and aged monkeys. 20,29 It has been shown that this cognitive func- 35,36 and that dysfunction in prefrontal cortex causes schizophrenia. [17][18][19] Our results of a correlation between cognitive dysfunction and abnormality in the function of dopamine receptors in haloperidol-treated monkeys suggest that dopamine receptor activity may play an important role in cognitive processing and that it may be a key to the schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…20,29 Animals that showed significant reduction in performance on the spatial delayed response task after treatment with haloperidol were considered cognitively-deficient.…”
Section: Haloperidol Treatment and Cognitive Statusmentioning
confidence: 99%